Styles of Knowledge Production in Colombia, 1850-1920 (2016)
Argument Using the notion of styles of knowledge we refer to the ways diverse scientific communities claim to produce true knowledge, their understandings regarding the attitudes and values that scientists should have in order to grasp natural and social reality, and the practices and technologies developed within such styles. This paper analyzes scientific and medical enterprises that explored the relationship between environment, population, and society in Colombia between 1850 and 1920. We argue that similar styles of knowledge production were shared in human geography, medical geography, and climatic physiology at the mid-nineteenth century; and that some physicians working in bacteriology and physiology since the 1880s established epistemic boundaries between their work and earlier scientific activities, while others found these distinctions irrelevant. However, the historical actors committed to any of the styles of knowledge production explored in this article agreed on the local specificity of their objects of inquiry, therefore questioning European science. These styles of knowledge production also shaped different ways of perceiving and addressing national problems. Hence, this article is a contribution to the recent literature on both historical epistemology and social and cultural history of science and medicine. © Copyright Cambridge University Press 2016.